Multipoint aerial refueling : a review and assessment - Killingsworth, Paul S.; Rand eBooks (Santa Monica, CA : RAND, 1996)
The U.S. Air Force currently relies principally on boom-and-receptacle technology to conduct aerial-refueling operations for fixed-wing aircraft. With this approach, a single aircraft at a time may be refueled behind a tanker. An alternative concept, called multipoint aerial refueling, uses probe-and-rogue technology to enable more than one aircraft to refuel simultaneously from a tanker. The work described in this documented briefing reviews five studies to determine whether any general conclusions may be drawn regarding the merits of multipoint aerial refueling. It also describes the results of a RAND analysis of how multipoint refueling might have affected tanker requirements during a single high-tempo day of Desert Storm operations. The work is part of a larger effort undertaken by RAND at the request of the Commission on Roles and Missions of the Armed Forces, to review and evaluate "current allocations among the Armed Forces of roles, missions, and functions" and to "make recommendations for changes in the current definition and distribution of those roles, missions and functions" (National Defense Authorization Act for FY 1994). As such, the document should be of interest to those Air Force and other U.S. military personnel, analysts, policymakers, and operational commanders who are broadly concerned with the employment of forces and with aerial-refueling operations in particular.
"National Defense Research Institute."
Annotated briefing.
Includes bibliographical references (p. 65).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Airplanes -- Air refueling; Airplanes, Military -- United States; Electronic books